2017
DOI: 10.1371/journal.pone.0179254
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of Elvitegravir/Cobicistat/Emtricitabine/Tenofovir Disoproxil fumarate in a real life setting: Data from surveillance cohort long-term toxicity antiretrovirals/antivirals (SCOLTA) project

Abstract: ObjectivesThe study aim was to evaluate the impact on Liver and Kidney toxicity of the single tablet regimen Elvitegravir/Cobicistat/Emtricitabine/Tenofovir Disoproxil Fumarate (EVG/COBI/FTC/TDF) on Antiretroviral Therapy (ART) experienced or naïve patients.MethodsPatients initiating EVG/COBI/FTC/TDF were enrolled in the SCOLTA project, a multicenter observational study reporting grade 3–4 Adverse Events in subjects beginning new antiretroviral drug regimens. In this analysis, patients were evaluated at T0 (ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…The observed kinetics of biomarker changes and kidney function decline within the first year following TDF initiation are also concordant with reported TDF-associated eGFR SCr declines that subsequently plateau at 6 months to 1 year. [45,46] In another study using this cohort of new TDF users, we have demonstrated that 6 of these 14 biomarkers, including β2M, KIM-1, clusterin, UMOD, cystatin C, and IL-18, were independently associated with eGFR decline during follow-up. [47] The recent introduction of tenofovir alafenamide fumarate (TAF), a less nephrotoxic alternative to TDF, has eased some concerns regarding tenofovir-associated nephrotoxicity.…”
Section: Discussionmentioning
confidence: 78%
“…The observed kinetics of biomarker changes and kidney function decline within the first year following TDF initiation are also concordant with reported TDF-associated eGFR SCr declines that subsequently plateau at 6 months to 1 year. [45,46] In another study using this cohort of new TDF users, we have demonstrated that 6 of these 14 biomarkers, including β2M, KIM-1, clusterin, UMOD, cystatin C, and IL-18, were independently associated with eGFR decline during follow-up. [47] The recent introduction of tenofovir alafenamide fumarate (TAF), a less nephrotoxic alternative to TDF, has eased some concerns regarding tenofovir-associated nephrotoxicity.…”
Section: Discussionmentioning
confidence: 78%
“…26 Over 6–12 months of follow-up in the SCOLTA cohort, only 1% of ART-naïve and 1% of ART-experienced PLWH using EVG experienced a severe LCE. 15 Finally, in a 3-year study in Spain of RAL users, only 1% of PLWH developed a grade 3 or 4 hepatotoxicity which were attributed to HCV co-infection. The cumulative incidence of any hepatotoxicity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many patients are diagnosed at late stage with a low immune recovery (23). Second, since it is a chronic disease that needs life-long treatment, HIV is burdened with a lot of co-morbidities due to the virus and treatment thereof (17). The safe profile showed by entry inhibitors could represent advancement in terms of drug-related toxicities in comparison with actual HAART.…”
Section: Discussionmentioning
confidence: 99%
“…The mean maximum reduction in HIV-1 RNA observed for the 324 mg weekly dose was 1,65 log. Individual viral nadirs were typically observed on day 22 (range, day [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Ccr5 Antagonistmentioning
confidence: 99%